Computation of Control for Linear Approximately Controllable System Using Tikhonov Regularization. (17th February 2018) - Nair, M. Thamban; Sukavanam, N.; Katta, Ravinder
ABSTRACT: Computation of control for a controlled partial differential equation is a diﬃcult task, especially when the control problem is ill posed. In this paper, we propose a method of computing the regularized control of a diffusion control system using Tikhonov regularization approach when the system is approximately controllable. The method proposed here for choosing regularization parameter guarantees the convergence of the proposed control.